PISA 2009/2000 en América Latina: una relectura de los cambios en el desempeño lector y su relación con las condiciones sociales - Guadalupe Mendizábal, César (2013)
This paper explores to what extent changes in performance of secondary education students between 2000 and 2009 for the Latin American countries participating in the OECD’s Programme for International Student Assessment (PISA) are explained by changes in the socio-economic conditions of the studied populations. To this end, the authors reprocess PISA data concluding that, as expected given the existing body of literature, changes in the socio-economic background of the populations under scrutiny play a very important role inexplaining the observed changes in the performance of students. Moreover, a different procedure is used for measuring the socio-economic background and this procedure ended up, for the five countries included in the analysis, being more sensitive to the contextual characteristics to which this data refers to.